Oral receptivity of Aedes aegypti formosus from Franceville (Gabon, central Africa) for type 2 dengue virus - (:unkn) unknown (My University, 1999)
Dengue is widely distributed in the tropics but epidemic activity was rarely reported in Africa before the 1980's. In the past 15 years, increased epidemic dengue fever has been reported both in East and West Africa, raising concern about the ability of local populations of Aedes aegypti to transmit dengue viruses. Ae. aegypti is present in two forms in Africa: Ae. aegypti aegypti and Ae. aegypti formosus. This latter form, much darker, was not originally a local species but is now colonizing artificial breeding sites within cities. We have been able to demonstrate the oral susceptibility for dengue type 2 virus of Ae. aegypti formosus collected in Franceville, Gabon (Central Africa). However, these mosquitoes sampled exhibited lower infection rates than those of a control colony of Ae. aegypti aegypti originating from French Polynesia.
Keywords: African Research